High Grade Myofibroblastic Sarcoma of Paratesticular Soft Tissues - Ioannis Anastasiou; Panagiotis K. Levis; Ioannis Katafigiotis; Georgios Karaolanis; Viktoria-Varvara Palla; Evangelos Felekouras; Antonios Athanasiou; Marina Perdiki; Dionysios Mitropoulos; Constantinos A. Constantinides (Case Reports in Oncological Medicine)
Tumors of the paratesticular region most often arise from the soft tissue surrounding the spermatic cord and the epididymis or from the soft tissue (dartos muscle) of the scrotal wall. Paratesticular tumors, despite their rarity, present a high incidence of malignancy (30%), and the therapeutic approach of choice is surgical resection with negative margin. The grade, the histology type, the presence of metastases during the diagnosis, the size of the tumor, the age of the patients, and the surgical margins are all important prognostic factors. We present a case report of a 86-year-old patient with a high grade paratesticular and scrotum sarcoma of soft tissues which was presented as a hard painful mass of the scrotum. The patient was subjected to high ligation of the spermatic cord and received no further treatment and 6 months after the operation no local or systematic recurrence was observed.